Why the assembly disbanded - Tejada, Roberto (Fordham University Press, 2022)
"Pushing the boundaries of Latinx literature and what constitutes a borderlands poetics Throughout Roberto Tejada's body of work, the renowned poet and celebrated critic has explored themes of Latinx culture, politics, history, language, and ecologies. In his latest collection, Why the Assembly Disbanded, he presents a unique contribution to Latinx letters that reflects on the relations between the U.S. and Latin America, especially their real and symbolic borderlands. Immersive, postmodern, and philosophical, Why the Assembly Disbanded provides an associative, critical Latinx aesthetic connecting the Mexico-U.S. borderlands to Latin America's neo-baroque heritage. Migrants, settlers, tourists, and exiles moving across various hemispheric landscapes are featured in these exuberant, capacious, and self-reflexive poems. Tejada relates the ravages of white supremacy in our culture that, together with immigrant precarity, turn home into a place of foreboding and impending eviction, even as a dream-weather makes room at last for scenes of possibility and attainment in the account of human history. The sweeping futuristic vista gives on to narratives of colonial extraction, human displacement, abuses of capitalism, mass media spectacle, the antagonism of language and technical images in the sensorium of urban and digital life-worlds, and the relations of desire encouraged by pictures and words in the economy of attention. Los Angeles and Mexico City figure prominently in poems committed to voicing modes of formation and community in an intersectional reckoning of personhoods prompted in work by artists Betye Saar, Amiri Baraka, Connie Samaras, and Ruben Ortiz Torres. With language given to pageantry, tonal precision, and a hopeful lyric radiance that can accommodate ecstasy and justice, Roberto Tejada's carnivalesque, borderland imagery pushes the boundaries of Latinx literature. World building by way of reverie, speculation, and retro-futurist tableaux, and with vivid, sometimes violent particularity, his poems enact hallucinatory realities of the hemisphere; an imagination that triangulates history, lyricism, and art as social practice"--